The Role of Scientific Research in Economic Development - Khasankhonova Nodira Isametdinovna (Research Parks Publishers, 2022)
In the article is considered the real state of products’ science-intensiveness in the country. In particular, the category of science intensity of products, its main constituent factors such as research, development, inventions, R&D costs, innovative products are discussed. In the article analyzed the Decree of the President of the Republic of Uzbekistan dated April 1, 2021 No. DP-5047